A Randomized Controlled Trial on Mutual Support Group Intervention for Families of People With Recent-Onset Psychosis: A Four-Year Follow-Up - Chien, Wai Tong; Bressington, Daniel; Chan, Sally W. C. (Frontiers in Psychiatry, 2018)
Introduction: Recent research in Western countries has indicated that family interventions in schizophrenia and other psychotic disorders can reduce patient relapse and improve medication compliance. Few studies have addressed Chinese and Asian populations. This study tested the long-term effects of a 9-month family-led mutual support group for Chinese people with schizophrenia in Hong Kong, compared with psycho-education and standard psychiatric care. Methods: A randomized controlled trial of Chinese families of patients with recent-onset psychosis (≤5 years of illness) conducted between August 2012 and January 2017, with a 4-year follow-up. Two hundred and one Chinese families of adult outpatients with recent-onset psychosis were randomly selected from the computerized patient lists and randomly assigned to either mutual support, psycho-education, or standard care group (n=70 per group). Family caregivers were mainly parent, spouse or child of the patients. Mutual support and psycho-education group consisted of 16 two-hour group sessions and patients participated in three sessions. The standard care group and the two treatment groups received the routine psychiatric outpatient care. Results. Patients and families in the mutual support group reported consistently greater improvements in overall functioning [family functioning, F(2, 203)= 8.13, p= 0.003; patient functioning, F(2, 203)= 6.01, p= 0.008] and reductions in hospitalization duration [F(2, 203)= 6.51, p= 0.005] over the 4-year follow-up. There were not any significant increases of medication dosages or service use by both the family support and psycho-education groups over time. Conclusions. The peer-led family support group can be an effective psychosocial intervention in early psychosis indicating long-term benefits on both patient and family functioning and re-hospitalizations. Clinical Trial Registration: NCT00940394: https://register.clinicaltrials.gov.